PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA ASN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS SOSIAL KABUPATEN SITUBONDO - Wati, Yulia Ika; Tulhusnah, Lusiana; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of the study was to determine the influence of leadership and work environment on ASN performance with work motivation as an intervening variable at the Situbondo Social Service. The sampling technique used in this study is a saturated sample. So the research sample is 33 respondents. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that leadership has a positive and significant effect on work motivation, work environment has a positive and significant effect on work motivation, leadership has a positive and significant effect on ASN performance, work environment has a negative and insignificant effect on performance ASN, work motivation has a positive and significant effect on ASN performance, leadership has a positive but not significant effect on ASN performance through work motivation, work environment has a positive and significant effect on ASN performance through work motivation.